2015
DOI: 10.1039/c5ra19343e
|View full text |Cite
|
Sign up to set email alerts
|

High-performance perovskite solar cells fabricated by vapor deposition with optimized PbI2 precursor films

Abstract: High-performance CH3NH3PbI3 solar cells were achieved by hybrid physical–chemical vapor deposition (HPCVD) method with optimized spin coating process for PbI2 precursor films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…52 The lm morphology, thickness, stoichiometry, crystallinity as well as material purity have signicant impact on the overall solar cell performance. A variety of solution-and vapor-based OHP deposition techniques have been reported including one-step spin-coating, [53][54][55][56][57] two-step deposition techniques, 41,58-60 solventsolvent extraction, 61 vapor-assisted solution processes, [62][63][64][65][66][67][68][69] dualsource vacuum deposition, 4,5,[70][71][72][73][74][75][76][77] hybrid deposition, [78][79][80][81] hybrid chemical vapor deposition, [82][83][84][85][86][87] sequential vapor deposition, [88][89][90][91][92] ash evaporation, 93 etc. One-step spin-coating is one of the widely used methods because of its simplicity and low-cost.…”
Section: Introductionmentioning
confidence: 99%
“…52 The lm morphology, thickness, stoichiometry, crystallinity as well as material purity have signicant impact on the overall solar cell performance. A variety of solution-and vapor-based OHP deposition techniques have been reported including one-step spin-coating, [53][54][55][56][57] two-step deposition techniques, 41,58-60 solventsolvent extraction, 61 vapor-assisted solution processes, [62][63][64][65][66][67][68][69] dualsource vacuum deposition, 4,5,[70][71][72][73][74][75][76][77] hybrid deposition, [78][79][80][81] hybrid chemical vapor deposition, [82][83][84][85][86][87] sequential vapor deposition, [88][89][90][91][92] ash evaporation, 93 etc. One-step spin-coating is one of the widely used methods because of its simplicity and low-cost.…”
Section: Introductionmentioning
confidence: 99%
“…10 A variety of methods including solution processing, 11,12 vacuum deposition [13][14][15][16] and vapor-assisted solution processing, [17][18][19] HCVD, 20 HPCVD, 21,22 LPVASP 23 etc. have been applied to fabricate perovskite lms.…”
Section: -3mentioning
confidence: 99%
“…However, it is observed that the reaction kinetics need to be controlled and developed for consistent device performance and reproducibility. Thus, in view of these problems, vapor deposition [ 149 ], co-evaporation [ 150 152 ], electrodeposition [ 153 ], and hybrid deposition [ 154 , 155 ] techniques are much better in controlling the thickness and the reaction kinetics for the fabrication process of large-scale devices. Yang et al developed a CH 3 NH 3 I vapor-based approach for the deposition of perovskite layers in a nitrogen environment.…”
Section: Thin-film Perovskite Deposition and Stability Featuresmentioning
confidence: 99%